Screening of ZAT12 and GlyII wheat transgenics using seedling based assays for stress tolerance - Bhowmick, Pradipta; Suneja, Yadhu Suneja; Srivastava, Puja; Sharma, Achla; Bains, Navtej Singh (Journal of Cereal Research, 2016)
Single copy transgenics of Agrobacterium mediated wheat transformants were available for two genes- Zat12 and GlyII in the background of wheat cultivar DPW 621-50. Three homozygous transgenic lines carrying ZAT12 and three carrying GlyII were subjected to preliminary screening for water deficit and salinity stress respectively. An initial experiment was carried out to standardize the concentrations of PEG and NaCl using parental non- transformed line DPW 621-50. Seedlings were grown in vermiculite in propagation trays in a growth chamber maintained at 200C Â± 20C, 8/16 hours dark/light ZAT 12 homozygous progenies were screening using PEG at 25% and 30% concentration. Transgenics Z-8-12 and Z-15-10 showed significant improvement for shoot and root traits under PEG induced water deficit stress. In the best transgenic line, 45%, 20%, 33%, 22%, 24%and 20% improvement over DPW 621-50 was observed for root length, shoot length, fresh root weight, root dry weight, shoot fresh weight and shoot dry weight respectively under stress conditions. In a parallel experiment, all the three GlyII transgenics showed marked superiority over parental cultivar DPW 621-50. The best GlyII transgenic showed 25%, 19%, 12%, 22%, 26% and 22% improvement over PBW 621 for root length, shoot length, fresh root weight, root dry weight, shoot fresh weight and shoot dry weight respectively under stress conditions.